Simplify: (sin θ − cos θ)^2 − (sin θ + cos θ)^2 A) −4sin(θ)cos(θ) B) 2 C) sin^2 θ D) cos^2 θ
![Simplify sin θ cos θ2 sin θ cos θ2 A 4sinθcosθ B 2 C sin2 θ D cos2 θ class=](https://us-static.z-dn.net/files/d39/7d23400daf97d9635dc315315e0366b1.png)
Answer:
-4sinθcosθ
Step-by-step explanation:
Note:
1. (a + b)^2 = a^2 + 2ab + b^2
2. (a - b)^2 = a^2 - 2ab + b^2
3. sin^2θ + cos^2θ = 1
(sinθ -cosθ)^2 - (sinθ + cosθ)^2
= sin^2θ - 2sinθcosθ + cos^2θ - (sin^2θ + 2sinθcosθ + cos^2θ)
= sin^2θ + cos^2θ - 2sinθcosθ - (sin^2θ + cos^2θ + 2sinθcosθ)
= 1 - 2sinθcosθ - (1 + 2sinθcosθ)
= 1- 2sinθcosθ -1 - 2sinθcosθ
= - 2sinθcosθ - 2sinθcosθ
= -4sinθcosθ